A contribution to the theory of economic development and the demographic transition: fertility reversal under the HIV epidemic. (June 2020) - Gori, Luca; Lupi, Enrico; Manfredi, Piero; Sodini, Mauro
Abstract: According to the conventional theory of the demographic transition, mortality decline has represented the major trigger of fertility decline and sustained economic development. In Sub-Saharan Africa (SSA), the HIV/AIDS epidemic has had a devastating impact on mortality, dramatically reversing the long-term positive trend in life expectancies in high HIV-prevalence countries. Moreover, SSA is experiencing a delayed and slower fertility transition compared to other world regions and there is growing empirical evidence highlighting the potential for a paralysis, or even a reversal, of the fertility transition in countries with severe HIV epidemics. This work builds on a unified growth theory-like general equilibrium model combined with HIV spread, where mortality endogenously feeds back into fertility and education decisions. The model supports the evidence of an HIV-triggered fertility reversal in SSA via the fall in education and human capital investments due to increased adult mortality, which eventually breaks the switch from quantity to quality of children. Fertility reversal is predicted to be more likely to occur in countries experiencing severe HIV epidemics, and its effects may persist even under successful scenarios of HIV control. These results suggest that the alarming possibility of a paralysis in the fertility transition, which so far has aroused little concern among international organizations, e.g., in the last round of UN population projections, should be seriously considered with a view to prioritizing policy interventions.